Identification of virulence genes and antimicrobial resistance in Campylobacter spp. from sheep from the state of Pernambuco in Brazil (Research, Society and Development, 2022)
The objective of this study was to genetically identify virulence and antimicrobial resistance in DNA from Campylobacter spp. from sheep in the state of Pernambuco, Brazil. The presence of virulence genes was investigated from the polymerase chain reaction. The genetic profile of antimicrobial resistance in samples of sheep origin was investigated by sequencing of the 23S rDNA region to identify A2074G and A2075G mutations and gyrA gene fragments to identify C257T and A256G mutations. Forty samples of Campylobacter spp. Of these, 11 were from Campylobacter jejuni, 12 from Campylobacter fetus subsp. fetus and 17 Campylobacter coli from sheep herds. In virulence analysis, 37 samples (92.50%) were positive for the cdtA gene, 30 (75.00%) for cdtB and 28 (70.00%) for cdtC. In the cadF gene research, 38 (95.00%) samples were positive. For the racR, dnaJ and ciaB genes, 32 (80.00%), 19 (47.50%) and 8 (20.00%) positivity were respectively. Only one sample presented the pldA gene and none presented wlaN and virB11. In genotypic analysis of antimicrobial resistance, all samples had the C257T mutation in the gyrA gene, but the A256G mutation was absent. Mutations in 23S rDNA, A2074G and A2075G were also not identified. From the results obtained, we can observe the presence of most virulence genes researched, with high resistance to fluoroquinolones. Thus, studied samples of Campylobacter spp. demonstrated the potential to cause infection and stay in the hosts.